Matilda / [engl.] - Dahl, Roald (London : Puffin Books, 2022)
The much-loved Roald Dahl story, updated for a whole new generation of readers with an exciting new interior design and cover look. These books gave Matilda a hopeful and comforting message: you are not alone.Matilda is a brilliant child with a magical mind.But her parents have decided she's just a nuisance who wastes too much time on reading and stories. And her headmistress Miss Trunchbull is a terrible bully, who thinks children are rotten and awful and should be locked up. Now it's time for Matilda to find the power to change her story, and show them just how extraordinary children can be . . . The text in this edition of Matilda was updated in 2022 for young independent readers.
Keywords: Abenteuer; Zauberei; Mut; Heldin; Klassiker; Antolin ab Klasse 4